Collaborative Content Construction: A Pedagogical Architecture to support distance education - Ramos, David Brito; Ramos, Ilmara Monteverde Martins; Castro, Alberto; Oliveira, Elaine Harada Teixeira de (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2020: Anais do III Workshop on Advanced Virtual Environments and EducationDO - 10.5753/wave.2020.212070, 2021)
This work presents a proposal of pedagogical architecture called Collaborative Content Construction, which relies on the collective construction of knowledge through relational pedagogy, supported by the genetic epistemology of Jean Piaget. Pedagogical architectures represent a way of contributing to innovation in the use of technological support in learning. This proposal includes a methodology that simultaneously builds, collectively and interactively, knowledge, and also leads to the development of materials that benefit participants even after the end of the activity, because in addition to learning in the process, we expect resulting learning material to be more attractive to the students since it would be developed by their peers.